2001
DOI: 10.1159/000054702
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Release of Prolactin-Releasing Peptide in Rat Hypothalamus in Association with Luteinizing Hormone and Prolactin Surges

Abstract: Prolactin (PRL)-releasing peptide (PrRP) is a novel hypothalamic peptide reported to be a potent and specific stimulator of PRL secretion. This author recently reported that PrRP might play a significant role in mediating the steroid-induced PRL surge in the rat. In order to examine the secretory profile of PrRP in the rat hypothalamus before and during the luteinizing hormone (LH) and PRL surges, this study employed the push-pull perfusion technique and determined the in vivo release of PrRP and also of gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…Consequently, it is precluded that the observed effects on LH and PRL are based on a concurrent control by hypothalamic GnRH 24 or PRL-releasing peptide. 25 This fits with the data of Bogacka et al ., who found that GnRH did not affect PRL secretion in vitro . 26 Rather than being secondary to responses of PRL and the HPA axis, the decrease in LH and testosterone during hypoglycaemia may be a direct consequence of reduced glucose supply, and therefore may also be less adaptive to repetitions of this state.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, it is precluded that the observed effects on LH and PRL are based on a concurrent control by hypothalamic GnRH 24 or PRL-releasing peptide. 25 This fits with the data of Bogacka et al ., who found that GnRH did not affect PRL secretion in vitro . 26 Rather than being secondary to responses of PRL and the HPA axis, the decrease in LH and testosterone during hypoglycaemia may be a direct consequence of reduced glucose supply, and therefore may also be less adaptive to repetitions of this state.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the adaptation of PRL to recurrent hypoglycaemia leads us to suspect that gonadotrophins and PRL are differentially regulated following separate mechanisms. Consequently, it is precluded that the observed effects on LH and PRL are based on a concurrent control by hypothalamic GnRH 24 or PRL‐releasing peptide 25 . This fits with the data of Bogacka et al ., who found that GnRH did not affect PRL secretion in vitro 26 .…”
Section: Discussionsupporting
confidence: 87%
“…The PRPs are unlikely to be PRPs (31) but do, nevertheless, regulate LH secretion through likely hypothalamic mechanisms (32,33), and GnRH neurons are reported to express immunoreactivity for G protein-coupled receptor 10, the PRP receptor (34). We find here that neither PRP-20 nor PRP-31 has any discernable effects on GnRH neuron firing rate at 1 M concentrations.…”
Section: Discussioncontrasting
confidence: 49%
“…PrRP gene expression is directly regulated by gonadal steroid hormones because PrRP neurons in the medulla oblongata are co-localized with receptors for estrogen or progesterone (53). In addition, administering estrogen or progesterone to ovariectomized rats induces PrRP mRNA expression in the medulla oblongata, as well as release of PrRP in the medial POA (53, 68, 91). …”
Section: Biological Actions Of Prrp and Prrp2mentioning
confidence: 99%